2010
DOI: 10.1089/pho.2008.2475
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Irradiation (InGaAlP-660 nm) Increases Fibroblast Cell Proliferation and Reduces Cell Death in a Dose-Dependent Manner

Abstract: Our data support the hypothesis that the physiological state of the cells affects the LLLT results, and that high-metabolic rate and short- cell-cycle 3T3 cells are not responsive to LLLT. In conclusion, LLLT with a dose of 3 J reduced cell death significantly, but did not stimulate cell cycle. A LLLT dose of 21 J had negative effects on the cells, as it increased cell death and inhibited cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 39 publications
1
36
0
2
Order By: Relevance
“…We found that 16 J/cm 2 of laser irradiation did not affect RPE proliferation Nuclei were counterstained with DAPI and are shown in blue on the first day and even had a negative effect on the second day. This is similar with findings by Frigo et al [21] and AlGhamdi et al [22] in different cell types. A higher dose of LLLI would cause over-release of intracellular Ca 2+ and exhaust the ATP reserves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that 16 J/cm 2 of laser irradiation did not affect RPE proliferation Nuclei were counterstained with DAPI and are shown in blue on the first day and even had a negative effect on the second day. This is similar with findings by Frigo et al [21] and AlGhamdi et al [22] in different cell types. A higher dose of LLLI would cause over-release of intracellular Ca 2+ and exhaust the ATP reserves.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we concluded that LLLI promoted cell cycle progression by modulating cell cycle-specific proteins. However, the effects of LLLI on cell proliferation or cell cycle progression are mainly determined by cell type [21,23,24], cell metabolic rate [21], cell cycle period [21], and parameters of the laser instrument [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Frigo et al reported that 660-nm LPLI at 21 J/cm 2 negatively affected 3T3 murine fibroblast cells, as it increased cell death and inhibited cell proliferation (9). Our earlier study first reported that 632.8-nm LPLI at 60 J/cm 2 , which was named high-fluence, low-power laser irradiation (HF-LPLI), could induce cancer cell apoptosis, as evidenced by caspase-3 activation (35).…”
Section: Innovationmentioning
confidence: 99%
“…Another study tested the effects of red laser 660nm (150 and 1050 J/cm 2 ) on fibroblasts. 14 The group that received 1050 J/cm 2 at 48 h presented a delay in cell growth and higher rates of cell death. The authors suggested a dose dependency that can be determined from the dosage used and the time of irradiation.…”
mentioning
confidence: 98%
“…In cell cultures, any changes in the irradiation protocol can induce alterations in the outcome. 14 In clinical studies of chronic tendinopathy, high doses of laser (21 J) have yielded poor results. 15 On the other hand, a study of liver regeneration analysis in rats described a stimulation effect with a red laser with 22.5 J/cm 2 of energy density.…”
mentioning
confidence: 99%